Reservoir Characterization of the Nsukka Formation in Anambra Basin Using Surface Outcrops - Nwoye, John T.; Ikegbunam, Ifunanya C.; Nwoye, Emmanuel C. (European Journal of Applied Sciences, 2024)
The results of grain size analysis, using bivariate and multivariate method of describing environment of deposition showed that Nsukka Formation was deposited by tidal processes. The field mapping of the areas and the bivariate plots of the Mean against Sorting, Skewness against Sorting and discrimination functions of the grains revealed that sediments of the delineated stratigraphic units were deposited in Beach/shallow agitated marine environment.This was based on their sedimentological characteristic.The grain size histograms are dominantly unimodal but few samples indicates bimodal distribution pattern. The Unimodality of these grains may be because the sediments were deposited in one phase and have not undergone much reworking or re-deposition.Petrographic studies of the representative sandstone units show that they are litharenite that exhibit the relic bedding features.The sandstones are classified as poorly - well sorted, angular – sub rounded, submature and mature grain-sized.Porosity and permeability assessment of the grain size indicated the average porosity and permeability value of 49-31 and 34.15-3.68 millidarcy respectively. This showed that the sandstones of Nsukka Formation has a high porousity and permeableabilty ratio. However, the sandstones of Nsukka Formation can serve as a good reservoir due to its excellent permeability, while the shale part of the Formation can also serve as a seal/cap to the reservoir due to its poor permeability.